Étude préliminaire des effets in vitro des huiles essentielles de cinq plantes aromatiques (Lavandula sp., Origanum sp., Rosmarinus sp., Salvia sp. et Thymus sp.) sur les larves de la processionnaire du pin d'Alep - BABAZ, Mohammed; BAHAZ, Khodir (My University, 2022)
The processionary caterpillar is one of the main defoliators of Aleppo pine forests in the Mediterranean basin. The chemical fight against this pest is considered an effective means, but the problems of resistance and the harmfulness of pesticides have led to the obligation to find healthier and more effective alternatives, based on the use of natural products in order to biological control. This study is devoted to the valuation of the insecticidal potential of the essential oils of five aromatic plants belonging to the Lamiaceae family (Lavandula sp., Origanum sp., Rosmarinus sp., Salvia sp. and Thymus sp.) against the Aleppo pine processionary larvae. The results obtained in vitro, revealed a strong insecticidal activity on the larvae of this pest, the use of the essential oils of the five aromatic plants made it possible to observe mortality rates greater than 50% and 80% for all the doses tested. on the second and fifth day respectively. Observations show that processionary caterpillar larvae are sensitive to the effect of EOs from Origanum sp., Thymus sp. and Salvia sp. in comparison with that of HEs of Lavandula sp. and Rosmarinus sp. This work indicates that the essential oils of the tested plants can be a source of new effective bioactive molecules to carry out a biological fight against the Aleppo pine processionary caterpillar.
Keywords: Bio-control; aromatic plants; essential oils; pine processionary